Examining Religious Attitudes and Reproductive Behavior among Women Visiting Health Centers of Shahid Beheshti University of Medical Sciences - Fahimeh Hajizadeh; Giti Ozgoli; Marzieh Saei Gharenaz; Zohre Sheikhan; Malihe Nasiri; Sharareh Jannesari (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: Reproductive behavior is one of the crucial factors in population fluctuations. Decrease in fertility rate in Iran with the increasing median age in recent years, along with the aging population and shrinking young workforce are among major challenges of the future. Given the significance of the subject, this study aimed to determine the relationship between religious attitudes and reproductive behavior of women who visited health centers of Shahid Beheshti University of Medical Sciences in Tehran 2016. Method: This cross-sectional study included all women who went to health centers of Shahid Beheshti University of Medical Sciences. 200 of these women with inclusion criteria were selected via convenience sampling. A three-part questionnaire was used to collect data containing demographic information, religious attitudes, and reproductive behavior .To analyze the data, descriptive and analytical statistics were utilized. In this study, all the ethical issues were considered. Moreover, the authors declare no conflict of interest. Results: The results showed that the mean ±SD age of participants was 29.24±1.6 The mean ±SD number family size, number of children, age at marriage, duration of marriage, the time between the age at marriage and the first pregnancy were 3.16 ±0.79, 1.8±0.78 ,8.5±5.9 years; 24.74±24.79 months; and 21.02±4.47 years, respectively. The results also demonstrated that the level of religious attitudes was good in majority of samples (67.5%). Analysis of variance indicated a significant relationship between different levels of religious attitude and reproductive behavior. Conclusion: The findings of this study further corroborate the importance of religion in the reproductive behavior of people. It is recommended that when running educational programs, counseling be done in order to promote reproductive behavior. Besides, special attention should be given to the religious beliefs of individuals to foster these two important factors. For downloading the full-text of this article please click here.